2016
DOI: 10.3892/ol.2016.5182
|View full text |Cite
|
Sign up to set email alerts
|

Runx2 expression: A mesenchymal stem marker for cancer

Abstract: Abstract. The transcription factor runt-related transcription factor 2 (Runx2) is a master gene implicated in the osteogenic differentiation of mesenchymal stem cells, and thus serves a determinant function in bone remodelling and skeletal integrity. Various signalling pathways regulate Runx2 abundance, which requires a number of molecules to finely modulate its expression. Furthermore, this gene may be ectopically-expressed in cancer cells. Recent studies have reported the involvement of Runx2 in cell prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Its expression is high in pre-osteoblasts and in early osteoblasts, but decreases in mature osteoblasts [32]. However, RUNX2 is involved also in cellular transformation and appears upregulated in different solid tumors [9]. RUNX2 is ectopically expressed in melanoma and plays an important role in progression [7,8,33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its expression is high in pre-osteoblasts and in early osteoblasts, but decreases in mature osteoblasts [32]. However, RUNX2 is involved also in cellular transformation and appears upregulated in different solid tumors [9]. RUNX2 is ectopically expressed in melanoma and plays an important role in progression [7,8,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…RUNX2 overexpression has been reported in breast cancer, pancreatic cancer, prostate cancer, lung cancer, ovarian epithelial cancer and melanoma. In previous studies, we identified RUNX2 as a stemness marker for cancer [9,10] and observed higher levels of RUNX2 expression in thyroid cancer patients with bone metastases [11]. RUNX2 appears to be involved in the osteolytic process [7,12].…”
Section: Introductionmentioning
confidence: 91%
“…Furthermore, the TGFβ and WNT pathways are known to induce oncogenic EMT and signaling pathways [ 39 ]. Recently, we reported that the osteogenic transcription factor RUNX2 may be considered a mesenchymal stem cell marker for cancer and that overexpression of this gene in solid tumors such as prostate, breast, pancreatic and lung cancer is associated with bone metastases [ 40 ]. Abnormal mesenchymal cell differentiation and overexpression of proto-oncogenes and downregulation of onco-suppressors are involved in the pathogenesis of osteosarcoma, a devastating bone tumor with a poor prognosis that affects children and adolescents.…”
Section: Mscs and Cancermentioning
confidence: 99%
“…In general, transcription factors may affect cellular processes and trigger cellular transformation. RUNX2, the master transcription factor for osteogenic differentiation, is overexpressed in several tumor tissues, including pancreatic cancer, breast cancer, ovarian epithelial cancer, prostate cancer, lung cancer, thyroid cancer and in osteosarcoma [14]. Lectins are biomolecules holding at least one non-catalytic domain able to bind specific monosaccharides or oligosaccharides [15].…”
Section: Discussionmentioning
confidence: 99%